Compartment syndrome of the non-injured limb. Issue 4 (9th April 2020) - Anwer, Majid; Banerjee, Niladri; Agarwal, Harshit; Kumar, Subodh
Abstract : Compartment syndrome is a common limb-threatening entity in trauma. However, the occurrence of the same in the non-injured limb is rare. It seems to be multifactorial in origin, with abnormal positioning being the most common cause. We present such a case of well-leg compartment syndrome which was treated by an urgent fasciotomy. We emphasise on the fact that the diagnosis of compartment syndrome is clinical and the management remains the same irrespective of whether the limb has sustained an injury or not.